2021
DOI: 10.1093/brain/awab283
|View full text |Cite
|
Sign up to set email alerts
|

Elevated iron concentration in putamen and cortical speech motor network in developmental stuttering

Abstract: Theoretical accounts of developmental stuttering implicate dysfunctional cortico-striatal-thalamo-cortical motor loops through the putamen. However, the analysis of conventional MRI brain scans in individuals who stutter has failed to yield strong support for this theory in terms of reliable differences in the structure or function of the basal ganglia. Here, we performed quantitative mapping of brain tissue, which can be used to measure iron content alongside markers sensitive to myelin and thereby… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…R2* is also considered a measure of myelin, but the T2* contrast is particularly sensitive to iron, especially within the basal ganglia. Despite R2* differences being noted in adults with speech problems in the putamen and cortical speech motor network (developmental stuttering, Cler et al, 2021 ), and observed links between verbal memory and R2* in the ventral striatum ( Steiger et al, 2016 ), we did not see any evidence for R2* differences anywhere in the brain when comparing our TD and DLD groups.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…R2* is also considered a measure of myelin, but the T2* contrast is particularly sensitive to iron, especially within the basal ganglia. Despite R2* differences being noted in adults with speech problems in the putamen and cortical speech motor network (developmental stuttering, Cler et al, 2021 ), and observed links between verbal memory and R2* in the ventral striatum ( Steiger et al, 2016 ), we did not see any evidence for R2* differences anywhere in the brain when comparing our TD and DLD groups.…”
Section: Discussioncontrasting
confidence: 85%
“…A growing number of studies use these maps to understand brain–behaviour relationships ( Allen et al, 2017 ; Clark et al, 2020 ). Most recently, we have used MPMs and found elevated iron levels in the putamen and speech motor network in people who stutter ( Cler et al, 2021 ). However, this novel semiquantitative protocol has not yet been used to examine microstructure in children with neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several putamen metrics have been associated with executive function, including blood flow [ 66 ], structural atrophy [ 67 ], and functional connectivity [ 68 ]. Iron accumulation in the putamen has also been described in developmental stuttering [ 69 ] and CADASIL [ 70 ]. Although most studies of dietary iron and cognition have been in children or anaemic individuals, there is some evidence that high dietary iron associates with poorer cognition [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several putamen metrics have been associated with executive function, including blood flow [60], structural atrophy [61] and functional connectivity [62]. Iron accumulation in the putamen has also been described in developmental stuttering [63] and CADASIL [64]. How iron deposition could result in cognitive deficits requires further investigation.…”
Section: Discussionmentioning
confidence: 99%